Placenta Accreta Spectrum: Diagnostic Standards, Guideline Concordance and Contemporary Management - Palacz, Bartosz; Kubiś, Natalia Marianna; Teper, Maria Magdalena; Perz , Wiktor; Polus, Aleksander; Wrona , Julia Anna; Gluzicka, Anna; Olczyk , Liwia; Piotrowski , Jędrzej; Korolchuk , Anhelina (Journal of Education, Health and Sport, 2026)
Background. Placenta accreta spectrum (PAS) encompasses abnormal placental implantation with pathological trophoblastic invasion of the myometrium and, in severe cases, adjacent organs. Rising cesarean delivery rates have increased PAS incidence, making it a major cause of severe obstetric hemorrhage and peripartum hysterectomy. Optimal outcomes depend on accurate prenatal diagnosis and coordinated multidisciplinary management. Aim. To synthesize contemporary evidence and guideline recommendations on PAS diagnosis, classification, and management, focusing on imaging standards, operative strategies, and models of care. Material and Methods. A narrative review was based on a targeted search of PubMed/MEDLINE and professional society resources conducted between January 2018 and November 2025. Priority was given to 8 major guideline documents and 5 systematic reviews/meta-analyses; additional observational studies were included for clinical and organizational context. Results. Guideline documents consistently recommend ultrasound as the first-line test for PAS, with MRI reserved for selected cases requiring additional anatomical detail. Planned cesarean hysterectomy without attempted placental removal remains the standard approach for most invasive PAS. Evidence for conservative management and interventional radiology (IR) adjuncts is inconclusive, and recommendations vary. Centralized care and multidisciplinary team management are repeatedly associated with improved maternal outcomes. Conclusions. PAS requires standardized diagnostic pathways and coordinated MDT care in specialized centers. Core recommendations align on early prenatal diagnosis (ultrasound with selective MRI) and planned cesarean hysterectomy for most invasive disease. Uncertainty persists for conservative strategies and IR adjuncts; ongoing prospective studies may inform future guideline updates and refine operative pathways, improving maternal safety and outcomes.